ANALYSIS DEALER NETWORKS IN RUSSIA - L. Alimova (Вестник университета, 2018)
The article presents analytical data on the effectiveness of sales through dealer networks in Russia and in Europe, as well as their growth prospects for 2018. Against this background the quantitative dynamics of dealer centers in Russia for the period from 2013-2017. The factors of influence of economic instability on dealer networks, as well as examples of closing of the largest dealer centers in Russia, are given. The zones of opening of new dealer centers in the regions of the Russian Federation by the largest global concerns are listed.